Study of snack bar combination of banana flour (Musa paradisiaca) and mung bean flour blending as emergency food. Issue 1 (April 2020) - Mahendradatta, M; Laga, A; Nurhisna, N I U
Abstract: The condition where refugees cannot fulfilling their food needs increases the need for emergency food production which is ready to consume. Emergency food can be design as a snack bar that can be produced using blended flour of banana, mung beans, and mung bean sprouts. The purposes of this study were to determine the best formulation of the snack bar and to determine the adequacy of snack bar nutrition content with nutritional adequacy rates per day. This study consists of two stages, first, the determination of the three best formulations from five formulations that have been made through organoleptic testing. The second stage was to determine the nutritional profile from the results of the first phase of research with observational parameters. Based on the organoleptic test results, and make the nutritional profile test results from 3 treatments were respectively water content (5.1%, 5.26%, 5.07%), ash content (2.53%, 2.59%, 2.69%), protein content (9.49%, 9.14%, 8.99%), fat content (19.56%, 19.38%, 19.34%) carbohydrate levels (63.33%, 63.62%, 63.92%), fiber content (1.35%, 1.44%, 1.48%), while for consecutive calorie calculation results (707.99 Cal, 708.59 Cal and 710.6 Cal).The conclusion is Snack bar can fulfill nutritional adequacy rates per day.